2017
DOI: 10.1038/jhg.2017.87
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association analysis identifies NMNAT2 and HCP5 as susceptibility loci for Kawasaki disease

Abstract: Kawasaki disease (KD), a systemic vasculitis of infants and children, manifests as fever and mucocutaneous inflammation. Although its etiology is largely unknown, the epidemiological data suggest that genetic factors are important in KD susceptibility. To identify genetic variants influencing KD susceptibility, we performed a genome-wide association study (GWAS) and replication study using a total of 915 children with KD and 4553 controls in the Korean population. Six single-nucleotide polymorphisms (SNPs) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 44 publications
2
23
0
Order By: Relevance
“…34 The HCP5 gene variants have been associated with a number of immune-mediated conditions such as HIV-1 control, 35 drugrelated Stevens-Johnson syndrome, 36 systemic lupus erythromatosus, 37 psoriasis, 38 and Kawasaki disease. 39 In AITD, the HCP5 polymorphism was first associated with thyroid peroxidase antibody levels/positivity in a multicentre population-based GWAS performed by Medici et al 31 Afterwards, we also demonstrated that the same HCP5 variant (rs3094228) was associated with susceptibility to GD in the Polish-Caucasian population. 40 In the current study, we identified HCP5 as one of POGD risk loci and showed that the number of HCP5 risk alleles is inversely correlated with age of GD onset.…”
Section: Hcp5supporting
confidence: 61%
“…34 The HCP5 gene variants have been associated with a number of immune-mediated conditions such as HIV-1 control, 35 drugrelated Stevens-Johnson syndrome, 36 systemic lupus erythromatosus, 37 psoriasis, 38 and Kawasaki disease. 39 In AITD, the HCP5 polymorphism was first associated with thyroid peroxidase antibody levels/positivity in a multicentre population-based GWAS performed by Medici et al 31 Afterwards, we also demonstrated that the same HCP5 variant (rs3094228) was associated with susceptibility to GD in the Polish-Caucasian population. 40 In the current study, we identified HCP5 as one of POGD risk loci and showed that the number of HCP5 risk alleles is inversely correlated with age of GD onset.…”
Section: Hcp5supporting
confidence: 61%
“…A total of 4,553 controls with no history of KD were obtained from the adult health cohort of the general population in Korea, which included 1,000 controls used in the initial GWAS and 3,500 controls used in the replication study. The GWAS was initially performed using our previous Illumina HumanOmni1-Quad BeadChip data (296 KD patients and 1,000 healthy controls) [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Susceptibility genes for KD (5-16) HLA, HCP5, FCGR2A, BLK, SLC8A1, CD40, NMNAT2, DAB1, COPB2, NAALADL2, IGHV, ZFHX3, NFKBIL1, ERAP1, EBF2, CACNB2, LTA, and LEF1 SNP in SLC8A1 (calcium signaling pathway) can be proof for using calcineurin inhibitors in KD and LEF1) (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) to the risk of cardiovascular disease in KD (TIAM1, NEBL, PLCB4/PLCB1, TUBA3C, SLC8A1, PELI1, KCNN2, TIFAB, and AGT) (8,12,(17)(18)(19)(20)(21)(22) and to the risk of intravenous immunoglobulin (IVIG) resistance (BCL2L11 and SAMD9L) (23,24). Involvement of the HLA region in susceptibility to KD has been controversial and has not been replicated across different ancestral groups.…”
Section: Related Risk and Referencesmentioning
confidence: 99%